Comparison of carbon uptake strategies between Chara aspera and Chara tomentosa growing in the brackish Baltic Sea and in the freshwater lakes of Estonia - Albert, Gerli; Pajusalu, Liina; Pritchard, Daniel W.; Hepburn, Christopher D.; Torn, Kaire; Paalme, Tiina; Põllumäe, Arno; Martin, Georg (Frontiers in Freshwater Science, 2024)
The carbon acquisition strategies of aquatic photosynthetic organisms play a key role in the growth and survival of a species. There is much research indicating that the predicted changes (e.g., the balance between carbonate species: CO2, HCO3 -, CO3 2-) in the seawater carbonate chemistry, due to ocean acidification, could affect benthic primary producers and their communities.However, considerably less is known about brackish water (e.g., the Baltic Sea), and even less about the possible effects of acidification on freshwater biota. This study aimed to compare the carbon uptake strategies of two dominant charophyte species: Chara aspera and Chara tomentosa growing in freshwater lakes of Estonia and in the brackish NE Baltic Sea. This could indicate how they might respond to the predicted increasing CO2 concentration linked to climate change scenrios. Carbon use strategies in charophytes were determined by analysing natural carbon isotope signatures (δ 13 C), pH drift experiments and photosynthesis vs. dissolved inorganic carbon curves. The study showed that freshwater and brackish water C. aspera and C. tomentosa likely use different carbon uptake mechanisms. Our results indicated that freshwater charophytes preferentially use CO2 and brackish water charophytes HCO3 -, likely due to their local acclimatization to different growth environments. Also, C. tomentosa and C. aspera from the studied lakes are likely carbon saturated (photosynthetic processes are operating at their maximum efficiency due to the availability of dissolved inorganic carbon in their environment) and probably will not gain photosynthetic advantages from acidification. However, the predicted increase in CO2 concentration may positively affect the growth of the charophytes in the brackish Baltic Sea.